2007
DOI: 10.1177/0011000006295149
|View full text |Cite
|
Sign up to set email alerts
|

The Meta-Analysis of Clinical Judgment Project

Abstract: Clinical and educational experience is one of the most commonly studied variables in clinical judgment research. Contrary to clinicians' perceptions, clinical judgment researchers have generally concluded that accuracy does not improve with increased education, training, or clinical experience. In this meta-analysis, the authors synthesized results from 75 clinical judgment studies where the experience of 4,607 clinicians was assessed in relation to the accuracy of their judgments about mental health (e.g., di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 154 publications
(130 reference statements)
3
62
2
4
Order By: Relevance
“…While it is self-evident that clinical psychologists who have worked longer in the field gain more experience, it has also been shown that they do not necessarily gain more expertise in psychodiagnostic decision-making (Spengler et al, 2009;Vollmer et al, 2013): Even after years of experience, clinical psychologists are relatively poor at categorizing mental disorders into DSM categories (Brailey et al, 2001;Schulte-Mecklenbeck et al, 2015) and make judgments strikingly similar to those of novices (e.g., AEgisdóttir et al, 2006;Garb, 1998;Strasser & Gruber, 2004;Witteman & Van den Bercken, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is self-evident that clinical psychologists who have worked longer in the field gain more experience, it has also been shown that they do not necessarily gain more expertise in psychodiagnostic decision-making (Spengler et al, 2009;Vollmer et al, 2013): Even after years of experience, clinical psychologists are relatively poor at categorizing mental disorders into DSM categories (Brailey et al, 2001;Schulte-Mecklenbeck et al, 2015) and make judgments strikingly similar to those of novices (e.g., AEgisdóttir et al, 2006;Garb, 1998;Strasser & Gruber, 2004;Witteman & Van den Bercken, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We expected to find no differences in psychodiagnostic accuracy between novices and experienced clinical psychologists on the clinical tasks (cf. Spengler et al, 2009); and we expected clinical psychologists to perform better than control participants on the clinical tasks, as these required domain specific knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the small effect of experience on diagnostic accuracy described in the meta-analysis by Spengler et al (2009), the effect of experience has not been significant in our studies because of methodological limitations, as discussed in chapters 2 and 3. Careful selection of novice, experienced and expert psychologists (cf.…”
Section: Experiencementioning
confidence: 90%
“…In general, research showed that experience is not associated with better clinical decisions (Dawes, 1996;Faust, 1986;Garb, 1998;Lichtenberg, 1997). However, a recent meta-analysis on the effect of experience on clinical decision making showed a small but reliable and positive effect of experience on diagnostic accuracy (Spengler et al, 2009). This effect was found across task situations, such as problem type or treatment decision, type of experience (clinical or educational) and breadth of experience (general or specific).…”
Section: Experiencementioning
confidence: 99%
See 1 more Smart Citation